ANALISIS TUGAS SEKRETARIS DALAM PENANGANAN SURAT MASUK DAN SURAT KELUAR PADA CV. SUMBER JAYA SERANG - Mujiaty, Yulia; Vidada, Irwin Ananta (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
Media use of letters has been known in human civilization for a long time. A letter is a means for delivering information in the form of a written statement to another party both on its own behalf (personal) and because of an official. The position of the letter can be said as a representation in the form of an expression or statement from the sender in communicating the matter conveyed. In brief, it can be stated that the letter is an important communication tool in the administration of work. Continuous correspondence relations, it is common for this activity to be referred to as correspondence or correspondence. the handling of correspondence activities both in the incoming letter and in the outgoing letter in the form of an effort to receive letters, grouping letters, directing letters and the process of efforts to record letters, distribute letters and send letters. The findings of the secretary's assignment in handling incoming letters and outgoing letters are found to be facts. Management of incoming letters has not been optimal and the outgoing mail has not been running optimally.